Study on the Influence of Green Bonds on Enterprise Green Innovation - Yi, Xinyu (International Journal of Global Economics and Management, 2025)
Green bond is a new financial instrument that balances economic benefits and environmental protection, and is crucial to accelerate the green transformation of enterprises. This paper takes enterprise issuing green bonds as a quasi-natural experiment, constructs a multi-point DID model to investigate how green bonds affect green innovation, and explores potential mechanisms. The findings indicate that: (1) Green bonds have the potential to greatly increase both the quantity and quality of green innovation within enterprises. (2) Mechanism test results show that green bonds mainly attract the attention of peers and intensify the research and development (R&D) competition by releasing green signals, and green innovation is promoted with R&D competition. (3) Heterogeneity test results show that the role of green bonds in promoting green innovation is more obvious in enterprises with high pollution and high ESG scores. In addition, belonging to the Green Finance Pilot Zones (GFPZ) will also affect the improvement of green bond issuance on green innovation. This study provides new insights for improving enterprises' green innovation and promoting China's green transformation.